Charlie Bone and the castle of mirrors - Nimmo, Jenny (New York : Orchard Books, 2005)
Charlie and his magically gifted friends and relatives work together to rescue Billy Raven, a young orphan, from a mysterious and dangerous couple who have adopted him.
5.0
3-6
3-6
Booklist
Voice of Youth Advocates (V.O.Y.A.)
770
Keywords: Orphans -- Fiction; Castles -- Fiction; Magic -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; England -- Fiction; Orphans -- Fiction; Castles -- Fiction; Magic -- Fiction; Private schools -- Fiction; School stories; England -- Fiction